2004
DOI: 10.1002/art.20472
|View full text |Cite
|
Sign up to set email alerts
|

Effective treatment of a mouse model of Sjögren's syndrome with eyedrop administration of anti‐CD4 monoclonal antibody

Abstract: Objective. To determine whether eyedrop administration of an anti-CD4 monoclonal antibody (mAb) is effective in the treatment of Sjögren's syndrome (SS) using a mouse model of the disease.Methods. The anti-CD4 mAb was administered daily into the eyes of mice with SS from ages 4 to 8 weeks or ages 10 to 12 weeks. During treatment, tear volume was monitored and after final treatment, histologic features of the lacrimal and salivary glands, the phenotypes and function of T cells, and serum titers of anti-␣-fodrin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0
1

Year Published

2005
2005
2014
2014

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 37 publications
1
8
0
1
Order By: Relevance
“…Analysis of Id3-deficient mice has demonstrated that aberrant T cells are sufficient for SS disease (5). Supporting a major role for CD4 ϩ T cells, eye drops containing anti-CD4 antibodies have been shown to reduce ocular symptoms in a different mouse model (20). Our analysis of r1⌬T͞r2n tends to support the conclusion that T cell-intrinsic defects can trigger SS-like disease.…”
Section: Discussionsupporting
confidence: 66%
“…Analysis of Id3-deficient mice has demonstrated that aberrant T cells are sufficient for SS disease (5). Supporting a major role for CD4 ϩ T cells, eye drops containing anti-CD4 antibodies have been shown to reduce ocular symptoms in a different mouse model (20). Our analysis of r1⌬T͞r2n tends to support the conclusion that T cell-intrinsic defects can trigger SS-like disease.…”
Section: Discussionsupporting
confidence: 66%
“…For instance, one of the promising agents is the anti-CD4 monoclonal antibody that was found to suppress the local activation of CD4+ T cells reducing the expansion of pathologic CD4+ T cells against α-fodrin in a mouse model of SS. 99 There are also a few studies suggesting that systemic linoleic and gamma-linolenic acids, and omega-6 essential fatty acids may reduce the underlying ocular infl ammation and in turn improve the signs and symptoms of ocular discomfort in KCS. 100,101 The possible mechanisms, benefi ts and risks of the abovementioned agents are summarized in Table 1.…”
Section: Novel Therapeutic Agentsmentioning
confidence: 99%
“…51 Similarly, topical application of an anti-CD4 monoclonal antibody to the eye also suppressed the local activation of CD4+ T cells rather than deleting them, which reduced the expansion of pathological CD4+ T cells against a-fodrin. 50 Ciclosporin A Although ciclosporin is not strictly considered to be a biological agent, we have included it here because this small fungal peptide acts by inhibiting nuclear translocation of the transcription factor NF-AT (nuclear factor of activated T cells). This leads to reduced transcription of several cytokine genes, including IL2, IL3 and IL4, and TNFa.…”
Section: Anti-cd4 Antibodymentioning
confidence: 99%